AMMA-CATCH, a Critical Zone Observatory in West Africa Monitoring a Region in Transition - S. Galle; M. Grippa; C. Peugeot; I. Bouzou Moussa; B. Cappelaere; J. Demarty; E. Mougin; G. Panthou; P. Adjomayi; E.K. Agbossou; A. Ba; M. Boucher; et al. (Vadose Zone Journal, 2018)
West Africa is a region in fast transition from climate, demography, and land use perspectives. In this context, the African Monsoon Multidisciplinary Analysis (AMMA)–Couplage de l’Atmosphère Tropicale et du Cycle eco-Hydrologique (CATCH) long-term regional observatory was developed to monitor the impacts of global change on the critical zone of West Africa and to better understand its current and future dynamics. The observatory is organized into three thematic axes, which drive the observation and instrumentation strategy: (i) analyze the long-term evolution of eco-hydrosystems from a regional perspective; (ii) better understand critical zone processes and their variability; and (iii) meet socioeconomic and development needs. To achieve these goals, the observatory has gathered data since 1990 from four densely instrumented mesoscale sites (∼10 km each), located at different latitudes (Benin, Niger, Mali, and Senegal) so as to sample the sharp eco-climatic gradient that is characteristic of the region. Simultaneous monitoring of the vegetation cover and of various components of the water balance at these four sites has provided new insights into the seemingly paradoxical eco-hydrological changes observed in the Sahel during the last decades: groundwater recharge and/or runoff intensification despite rainfall deficit and subsequent re-greening with still increasing runoff. Hydrological processes and the role of certain key landscape features are highlighted, as well as the importance of an appropriate description of soil and subsoil characteristics. Applications of these scientific results for sustainable development issues are proposed. Finally, detecting and attributing eco-hydrological changes and identifying possible regime shifts in the hydrologic cycle are the next challenges that need to be faced.